Rock protein as cardiac hypertrophy modulator in obesity and physical exercise - Anaruma, Chadi Pellegrini [UNESP]; Pereira, Rodrigo Martins; Cristina da Cruz Rodrigues, Kellen; Ramos da Silva, Adelino Sanchez; Cintra, Dennys Esper; Ropelle, Eduardo Rochete; Pauli, José Rodrigo; Pereira de Moura, Leandro [UNESP] (Elsevier, 2020)
Obesity and cardiovascular diseases are worldwide public health issues. In this review, we discussed the participation of ROCK protein in cardiac hypertrophy, mainly through the modulation of leptin and insulin signaling pathways. Leptin plays a role in cardiovascular disease development and, through the Rho-associated protein kinase (ROCK), promotes cardiac hypertrophy. ROCK protein, is regulated by small Rho-GTPases and has two isoforms with high homology. ROCK is able to activate the MAP kinase (MAPK) pathway and modulate insulin signaling in the heart, participating in cardiac hypertrophy development of concentric and eccentric left ventricle growth. Although different types of stimulus can lead to morphologically antagonistic heart growth, physical exercise promotes improvements in hemodynamic function, emerging as a promising non-pharmacological tool to improve overall health. Leptin can activate ROCK in a pathological way, increasing MAPK activity and decreasing insulin signaling via insulin receptor substrate 1 (IRS1) serine 307 residue phosphorylation, phosphatase and tensin homolog, and protein kinase Cβ2. In turn, physical exercise decreases leptin levels and positively modulates insulin signaling as well as increases ROCK-dependent IRS1 (Ser632/635) phosphorylation, improving phosphatidylinositol 3-kinase/protein kinase B axis and promoting physiologic heart growth. Currently, there is a lack of studies about differences in ROCK isoforms, especially during exercise and/or obesity. However, the understanding of its biological function and the complex mechanism underlying the distinct types of cardiac hypertrophy development can be a useful tool in the improvement and treatment of cardiovascular outcomes.
Keywords: Cardiac hypertrophy; Leptin; Obesity; Physical exercise; ROCK